Evaluation of iron deposition in brain basal ganglia of patients with Parkinson's disease using quantitative susceptibility mapping - Shahmaei, Vahid; Faeghi, Fariborz; Mohammadbeigi, Ahmad; Hashemi, Hasan; Ashrafi, Farzad (European journal of radiology Open, 2019)
Parkinson's disease is associated with iron deposition in the brain. The QSM (quantitative susceptibility mapping) is more sensitive than T2-weighted imaging, T2* and R2. Few studies have been used QSM to evaluate the iron in the basal ganglia of patients with Parkinson's disease. Our aim was to evaluate the iron deposition in the basal ganglia using QSM and determination of diagnostic value of this method and evaluation of the association between disease stage with QSM and age with QSM in all nuclei, separately. Thirty patients were tested using Hoehn and Yahr test in three different stages. Fifteen healthy subjects were considered as control group. MRI sequences were performed using SIEMENS 3 T scanner.The Signal Processing in NMR software was used to process and analyze the images. The QSM in every of the basal ganglia was measured separately. There was a significant difference for QSM in the Subtania Nigera, Red Nucleus, Thalamic Nucleus and Globus Pallidus nucleus between two groups. The relationship between disease stage with QSM was significant in Subtania Nigera, Red Nucleus, and Globus Pallidus nucleus. The QSM values had a significant association with disease stage in all nuclei. The results showed that QSM has a higher accuracy in Subtania Nigera, Globus Pallidus, Red Nucleus and Thalamic Nucleus, respectively. Using QSM in Red Nucleus, Subtania Nigera, and Globus Pallidus nuclei can help diagnosis and staging the patients with Parkinson's disease. In future, studies with emphasis on the disease stage can be helpful in evaluation the different parts of these three nuclei.